Najd before the Salafi Reform Movement: Social, Political and Religious Conditions during the Three Centuries Preceding the Rise of the Saudi State by Uwaidah M. Al Juhany. (Reading, UK: Ithaca Press, in association with the King Abdul Aziz Foundation for Research and Archives, Saudi Arabia, 2002. 223 pages.) (American Journal of Islam and Society, 2004)
As the Muslim world searches for the right formula for reform, scholarsand intellectuals are invited to study Islamic reform movements and theconditions that made their successes possible. In this context, Najd beforethe Salafi Reform Movement is a timely contribution to the literature onsocial conditions of reform in Muslim societies. The author correctly notesthat pre-Salafi Najd (central Arabia) was neither a center of religious learningnor the site of large urban communities, which might be expected toproduce a reform movement of a size and significance of the Salafi movement.Nevertheless, the Salafi movement managed to establish a strongstate that unified Arabia and imposed peace and order on its people for thefirst time since the period of the early caliphs (pp. 1-2).This book, originally a Ph.D. dissertation, seeks to solve this puzzle.A six-page bibliography and a thirteen-page index are suffixed, along withseveral maps and tables, and both the Hijri and the Gregorian calendars areused to mark the general time periods. This book is particularly useful forstudents of history, sociology, anthropology, or genealogy in an earlymoderncontext, such as that of Najd between the mid-ninth/fifteenth andmid-twelfth/eighteenth centuries. The author argues that nomadic migrationand settlement; the growth of a sedentary population, as well asmigration and resettlement; and the growth of religious learning combinedto create a new Najdi society that produced the Salafi reform movement(p. 2). Each of these factors is addressed in one chapter.The first chapter, “The Geographical and Ecological Background,”demonstrates how Najd’s geographical setting and climatic conditions(viz., a desert region with an unpredictable climate) dictated its people’shard lifestyle and activities. For example, a persistant drought could turn asettlement, a region, or even the entire emirate into a wasteland (pp. 36-37).The second chapter, “An Historical Background,” surveys Najd’s inhabitantsat the rise of Islam and follows its demographic and political developmentsthroughout the first 9 centuries of the Islamic era. On the eve ofIslam, Najd was populous and prosperous; however, by the third/ninth ...